Factors associated with vegetable and fruit intake among adolescents with overweight and obesity in Selangor from 2020 to 2021 - Shahridzal, Shaliza A.; Lau, May Y.; Abd. Talib, Ruzita; Mohd Saat, Nur Zakiah (Frontiers in Public Health, 2025)
BackgroundSubstantial scientific evidence firmly advocates consumption of vegetables and fruits for maintenance of overall health and protection against chronic diseases, such as obesity. However, prevalence of fruit and vegetable intake among adolescents in Malaysia remains low, whereas the data on factors associated with vegetable and fruit intake among adolescents were limited.ObjectiveThis study aims to determine the prevalence of fruit and vegetable intake and the factors that influence the Malaysian adolescents' consumption of fruits and vegetables.MethodsA cross-sectional study was conducted from November 2021 to August 2022 by distribution of an online validated questionnaire on various platforms to recruit school-going adolescents aged 13 to 17 years old (Form 1–5) in Selangor. Respondents were screened and data of eligible participants were included as subjects. Descriptive statistics, chi square analysis, and generalized linear model with Poisson-loglinear distribution and the robust estimator were employed for data analysis.ResultsA total of 277 adolescents participated in this study. Overall, low prevalence of adequate vegetable consumption was observed (23.5%). Of the participants surveyed, 14.8% of adolescents with thinness, 25.2% and 15.0% of adolescents with overweight and obesity, and 27.1% of normal-weight adolescents met the recommended daily intake (>3 servings), whereas 64.1% of adolescents with overweight and obesity and 65% of normal-weight participants consumed at least two servings of fruits a day. The findings revealed significant association between BMI-for-age (X2(1, N = 277) = 5.236, p = 0.022) and adolescent fruit intake. On the other hand, overweight and obese adolescents reporting positive intention (PR: 1.146, 95% CI: 1.002, 1.310, p = 0.047) and parental allowance (PR: 1.125, 95% CI: 1.011, 1.252, p = 0.030) were observed to have 14.6% and 12.5% higher prevalence of fruit consumption, respectively, while availability at home (PR: 0.849, 95% CI: 0.731, 0.987, p = 0.033) showed significantly lower prevalence of fruit intake with more reports of home availability.ConclusionThe study suggests that personal, social-environmental, and physical-environmental factors influence vegetable and fruit intake among adolescents, particularly fruit intake consumption behaviors among overweight and obese adolescent population in Selangor. The enunciation of these intake correlates could potentially be incorporated in future development of intervention strategies to effectively promote fruit and vegetable intake.